Depression among old age people (International Journal of Food and Nutritional Sciences, 2022)
Aging is the result of numerous internal biological and psychological changes that occur in agenetically mature body. Gradually, these modifications have a negative impact on the organism'sability to survive and adapt, which leads to the eventual occurrence of death